Development of a scale examining post-disaster coping motivations in Turkey after the 6 February earthquake - Sahin, Yahya; Okan, Nesrullah (Wiley, 2024)
ObjectivesThe aim of this study was to develop the Motivations for Coping After Disaster Scale. To test the construct validity of the scale, a total of 676 data were collected from three different sampling groups (N1: 388; N2: 194; N3: 94).MethodsExploratory Factor Analysis, Confirmatory Factor Analysis (CFA) and Criterion validity analysis were conducted to test the construct validity of the scale.ResultsAs a result of CFA, it was seen that the post-disaster scale had a five-dimensional structure (spiritual values, hope, friend support, solidarity, family support). The loadings of the items of the scale are at a good level. As a result of CFA, the scale was found to have acceptable and good fit indices (chi 2/sd = 2.690; RMSEA (Root Mean Square Error of Approximation) = 0.066; SRMR (Standardized Root Mean Square Residual) = 0.047; CFI (Comparative Fit Index) = 0.948; GFI (Goodness of Fit Index) = 0.917). The results of the criterion validity analysis show that the scale has criterion validity. Cronbach Alpha internal consistency coefficient shows that the scale is highly reliable (Total = 0.923).ConclusionsThe results of this study show that the Post-Disaster Coping Motivations Scale is a valid and reliable instrument. It is thought that the scale can make an important contribution to understanding psychological recovery processes after disaster and providing appropriate support to individuals.
Keywords: coping; disaster; scale development